Performance of buried HDPE pipes – part II: total deflection of the pipe. Issue 4 (18th April 2017) - Zhou, M.; Wang, F.; Du, Y. J.; Liu, M. D.
Abstract : Total deflection of buried thermoplastic pipes is extensively studied in previous work as it is a service limit state specified in design standards. In this paper, two-dimensional finite-element modeling is conducted to investigate the total deflection of buried high-density polyethylene (HDPE) pipes with a special consideration of the peaking behavior. The finite-element modeling method is evaluated using the data measured in a field trial which is presented in Part I. Parametric study are conducted. It is shown that the relative flexure stiffness, the type of compactor and the unit weight of soil cover have significant effects on the total deflection of the pipe. Based on analyses of the finite-element simulation results and experimental data, two empirical formulas with five parameters are proposed to describe the total deflection of HDPE pipes in both the vertical and horizontal directions. A comprehensive comparison is made between the calculated deflections made using the proposed equations and some existing methods and the measured data from published papers. It is seen that the proposed method significantly improves the accuracy of existing methods, and it also has advantages over existing methods because it has far fewer parameters and more convenient parameter determination.